Role of platelet activating factor in the intestinal epithelial secretory and Chinese hamster ovary cell cytoskeletal responses to cholera toxin. - Guerrant, R L (1994)
With the recent heightened concern about cholera around the world come new questions about the mechanism by which cholera toxin causes diarrhea. Peterson and Ochoa have suggested that prostaglandin synthesis is key to both the intestinal epithelial secretory and the CHO cell responses to cholera toxin [Peterson, J. W. and Ochoa, G. (1989) Science 245, 857-859]. Because platelet activating factor (PAF) can be a potent stimulus for prostaglandin synthesis, we examined its role in the intestinal and tissue culture effects of cholera toxin. We report that the specific PAF receptor antagonists BN 52021 and SR 27417 inhibit the effects of cholera toxin on intestinal secretion in rabbit ileal loops in vivo and on the cytoskeleton of Chinese hamster ovary cells in vitro. We also show that PAF itself can cause net fluid secretion in the rabbit model and that PAF potentiates the effects of cholera toxin on intestinal secretion. Finally, we demonstrate that cholera toxin stimulates significant PAF production (2.6-fold) in isolated T-84 intestinal epithelial cells. We conclude that cholera toxin stimulates PAF production and that PAF is involved in both the secretory and cytoskeletal responses to cholera toxin. These findings further support the involvement of additional mediators of cholera toxin effects other than mucosal cell cyclic AMP and help explain the effects of cholera toxin on prostaglandin synthesis.